Serious Bacterial Infections and Hepatitis C Virus Among People Who Inject Drugs: A Syndemic or Intertwined Epidemics? - Thomas J. Stopka; Robin M. Nance; L. Sarah Mixson; Hunter Spencer; Judith I. Tsui; Judith M. Leahy; Mai T. Pho; Jean DeJace; Judith Feinberg; April M. Young; Wei-Teng Yang; Amelia Baltes; et al. (Tropical Medicine and Infectious Disease)
Limited research has examined the possible synergistic interrelationships between serious bacterial infections (SBIs) of the heart (i.e., endocarditis), bone, spine, brain, or joints (e.g., osteomylelitis) and hepatitis C virus (HCV) infections. We examined whether syndemic interactions existed between SBI, HCV, and substance-use-related factors in rural communities, hypothesizing that injection-mediated risks elevated the likelihood for both SBIs and HCV infections, which could be exacerbated by synergistic biological–biological or biological and social interactions. We calculated the prevalence ratios (PRs) of past-year SBI associated with each risk factor in separate models. Effect modification among significant risk factors was assessed using multiplicative interaction. Among 1936 participants, 57% were male and 85% White, with a mean age of 36 years. Eighty-nine participants (5%) reported hospitalization for an SBI in the year prior to the survey. More than half tested HCV-antibody-positive (58%); 62 (5.6%) of the participants with a positive HCV antibody result reported past-year hospitalization with an SBI. Injection behaviors were correlated with other SBI risk factors, including multiple injections in the same injection event (MIPIE), injection equipment sharing, and fentanyl use. In adjusted models, MIPIE (PR: 1.79; 95% confidence interval [CI]: 1.03, 3.11) and fentanyl use (PR: 1.68; 95% CI: 1.04, 2.73) were significantly associated with past-year SBI. Our analyses pointed to co-occurring epidemics of SBI and HCV, related to the cumulative health effects of fentanyl use contributing to frequent injections and MIPIE. Both the SBI and HCV epidemics present public health challenges and merit tailored interventions.